Cardiac Tumor with Embolic Complication during Pregnancy - Zamudio, Romel (2020)
We present the case of a young pregnant woman in her first trimester, that presented with non-elevated ST myocardial infarction and left atrial myxoma. Despite the risk of cardiac surgery in a pregnant woman, the removal of the cardiac tumor was decided due to a high embolic risk. The surgery was performed without complications and following controls demonstrated fetal viability until delivery.